KONSEP DAN URGENSI PANCASILA SEBAGAI SISTEM ETIKA - Syajaro tuddur; Violla Wulandari; Suci Amelia; Yeti Murniati; Khairul Arifin; Bambang Trisno (Kampus Akademik Publiser, 2024)
Abstract. Pancasila, as Indonesia's moral and philosophical foundation, plays a crucial role in shaping society's morality and behavior. This article investigates the importance of Pancasila as an ethical system, combining historical, sociological and political approaches. We highlight the urgency of Pancasila in strengthening unity, justice and prosperity, as well as as a moral guide that promotes harmony and tolerance in a diverse society. In the era of globalization, understanding and implementing Pancasila is increasingly vital in building a sovereign and just country. The research method used is literature study, which allows in-depth analysis of various sources, including books, journals and official documents. Key findings highlight the importance of Pancasila in shaping national character and identity, while overcoming challenges such as changing values, conflict, corruption, and the influence of technology. In conclusion, Pancasila is not just a slogan, but an important foundation for national and state life in Indonesia.